THE INFLUENCE OF LIQUIDITY AND SOLVENCY ON PROFITABILITY IN METAL COMPANIES AND THE LIKE PERIOD 2010-2018 - Prima Putri, Septiani Rizki Amalia; Suparno, Suparno (Jurnal Ekonomi Balance, 2018)
This research aims to know The Effect of Liquidity as Current Ratio (CR) and Solvency as Debt to Equity Ratio (DER) partially and simultaneously on Profitability as Return On Asset (ROA) at Metal and Allied Company Listed On Indonesia Stock Exchange 2010-2018. The technique to determine the sample is Purposive Sampling and obtained 4 companies during 9 years of research. The research method was used descriptive verificative with multiple linear regression analysis. The result showed that Liquidity (CR) has a effect on Profitability (ROA), because thitung > tabl (2,977 > 2,040) and 0,006 < 0,05 of significant value. Solvency (DER) has no effect on Profitability (ROA) because thitung < ttabel (-0,415 < 2,040) and 0,681 > 0,05 of significant value. Liquidity (CR) and Solvency (DER) has a effect on Profitability (ROA), because fhitung > ftabel (9,209 > 3,28) and 0,001 < 0,05 of significant value.